Rancang Bangun Sistem Informasi Penjualan Genteng Kramik Pada CV. Putri Djaya Sentosa Jakarta - Siti Marlina; Titik Misriati; Rahmat Hidayat (LPPM Universitas Bina Sarana Informatika, 2020)
CV. Putri Djaya Sentosa Jakarta is a kind of business which is engaged in retail distributor and supplier of shops. The company is built beside the Owner's house, And the origin of its establishment started with the opening of the company in the area of Jl. Cabbage. Sugiono No.25 Duren Sawit East Jakarta. The growing of CV. Putri Djaya Sentosa Jakarta directly conduct checks on archives relating to sales, Archives that support the sales process is not small, so problems arise in the system is still done manually. For that we need computerization that can speed up the process of data processing so as to produce accurate and fast data to be built that most or at least reduce the level of errors that have been happening in the sales process. Once designed a sales information system containing goods sales data and goods sales reports.